Turn-Taking dalam Proses Pembelajaran Dosen dan Mahasiswa Universitas Merangin - Pratiwi, Anggia; Hartati, Hera; Oktawati, Herysa (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to analyze turn-taking patterns in academic discussions among students of the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, University of Merangin. The method used is a qualitative case study, involving 35 seventh-semester students as respondents. Data were collected through audio-visual recordings and field notes, then analyzed using the interactive model of Miles & Huberman with the turn-taking theory of Sacks et al., (1974) as the main framework. The results revealed that the dominant turn-taking patterns were “selecting oneself as the next speaker” (MDSPB) and “speaker continuing his turn” (PMG), which often manifested as interruptions. Uniquely, these interruptions were not always perceived negatively and instead reflected active participation, where the dynamics were strongly influenced by contextual factors such as Jambi Malay cultural background, gender, and the closeness of social relationships between participants. These findings provide an important contribution to the development of pragmatics and discourse analysis by offering a new perspective that turn-taking patterns are not only seen as violations, but also as complex and contextual communication strategies. The implications of the research results can be used as teaching materials in Pragmatics lectures to enrich understanding of the dynamics of conversation in academic spaces.